Power from on high the Spirit in Israel's restoration and witness in Luke - Acts - Turner, Max, 1947- (Sheffield, UK Sheffield, 1996)
Includes bibliographical references and index.
Keywords: Bible. N.T. Luke -- criticism, interpretation, etc; Bible. N.T. Acts -- criticism, interpretation, etc; Holy Spirit -- primitive and early church -- ca. 30-600.